2017
DOI: 10.5194/hess-21-6219-2017
|View full text |Cite
|
Sign up to set email alerts
|

Moment-based metrics for global sensitivity analysis of hydrological systems

Abstract: Abstract. We propose new metrics to assist global sensitivity analysis, GSA, of hydrological and Earth systems. Our approach allows assessing the impact of uncertain parameters on main features of the probability density function, pdf, of a target model output, y. These include the expected value of y, the spread around the mean and the degree of symmetry and tailedness of the pdf of y. Since reliable assessment of higher-order statistical moments can be computationally demanding, we couple our GSA approach wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 38 publications
1
75
0
Order By: Relevance
“…Note that relying on multiple statistical moments explicitly recognizes that variance is not an exhaustive metric to quantify sensitivity (e.g., Dell'Oca et al, 2017;Pianosi and Wagner, 2015;Borgonovo, 2007;Liu et al, 2006). Figure 1 depicts a sketch of the overall concept underpinning (1) when one considers two possible model choices, M 1 and M 2 , each associated with a set of two parameters, i.e., (θ 1 1 , θ 1 2 ) for M 1 and (θ 2 1 , θ 2 2 ) for M 2 .…”
Section: Water Resources Researchmentioning
confidence: 99%
“…Note that relying on multiple statistical moments explicitly recognizes that variance is not an exhaustive metric to quantify sensitivity (e.g., Dell'Oca et al, 2017;Pianosi and Wagner, 2015;Borgonovo, 2007;Liu et al, 2006). Figure 1 depicts a sketch of the overall concept underpinning (1) when one considers two possible model choices, M 1 and M 2 , each associated with a set of two parameters, i.e., (θ 1 1 , θ 1 2 ) for M 1 and (θ 2 1 , θ 2 2 ) for M 2 .…”
Section: Water Resources Researchmentioning
confidence: 99%
“…In this study we address this by limiting the parameter ranges of the multipliers where we suspect nonlinearity in the model response. In general the choice of the chosen global sensitivity method may yield different results (Dell'Oca et al, 2017). On the other hand, Janetti et al (2019) showed for a regional-scale groundwater study that different global methods showed similar results for hydraulic conductivity parameterization.…”
Section: Sensitivity Of Head and Surface Water Body Flow To Choice Inmentioning
confidence: 99%
“…Lastly, they show in which regions global groundwater models might benefit the most from efforts in improving global datasets like global hydraulic conductivity maps. (Reinecke et al, 2019) is a global groundwater model intended to be coupled with WaterGAP (Döll et al, 2003(Döll et al, , 2012Müller Schmied et al, 2014) and is based on the Open Source groundwater modeling framework G 3 M-f 1 (Reinecke, 2018). It computes lateral and vertical groundwater flows as well as surface water exchanges for all land areas of the globe except Antarctica and Greenland on a resolution of 5 arcmin with two vertical layers with a thickness of 100 m each, representing the aquifer.…”
mentioning
confidence: 99%
“…Here I aim to accelerate parameter optimization and uncertainty assessment of an LSM using the technique of statistical machine learning-based surrogate modeling, which is theoretically investigated in the field of applied mathematics called uncertainty quantification (Sullivan, 2015). Although this technique has been used for the parameter sensitivity analysis of atmospheric models (e.g., Qian et al, 2018), hydrological models (e.g., Dell'Oca et al, 2017;Maina & Guadagnini, 2018;Teixeira Parente et al, 2019), and ecological models (e.g., Hawkins et al, 2019), few studies have applied it to parameter optimization and uncertainty assessment of LSMs with globally applicable satellite observations. In this study, a statistical surrogate model, which can mimic the relationship between model parameters and gaps between simulation and observation, is developed using machine learning.…”
Section: Introductionmentioning
confidence: 99%